Histological changes in the amniotic membrane structure of gestational diabetic women’s’ in comparison with pregestational diabetic and non-diabetic women - Ali, Wafaa Idress; Waheed, Intissar Numman; Abdulla, Imad Taher (Technium BioChemMed, 2023)
The main objective of this study was to compare the demographic characteristics and histological changes in the amniotic membrane (AM) of gestational diabetes mellitus (GDM), pregestational diabetes mellitus (PGDM), and non-diabetic women. A total of thirty AM samples (n = 10 for each group) were obtained from full-term pregnant women without any complications. These samples were processed for paraffin blocks, sectioned, and stained with H&E. The results of demographic characteristics showed the mean maternal age of the PGDM and GDM groups was significantly higher compared with the control. Neonatal weight decreased significantly in the PGDM group, but both diabetic groups showed no significant differences between them in terms of maternal age and neonatal weight. A random blood sugar (RBS) test and WBC count showed a highly significant increase in GDM and a significant increase in PGDM. The highest significant value of RBC was recorded for PGDM. The thickness of the epithelial layer plus the basement membrane (BM) was significantly increased due to the PGDM. while the compact layer plus the fibroblast layer and the total thickness of AM showed a significant increase in GDM. The nucleus diameter of AM epithelial cells was significantly decreased in diabetic groups. The histological examination revealed that both diabetic groups caused several changes and damage in AM, including: hypertrophy and hyperplasia in epithelial cells associated with the formation of the vacuole between them; degeneration of some of these cells that pinched off from the lining epithelium; breakdown of the compact and fibroblast layers and caused damage to the stromal collagen fibril; epithelial cells and their nuclei became elongated and resembled columnar epithelium; and the basement membrane appeared thicker in comparison to the control group. In conclusion, GDM and PGDM induced various alterations and damage to the AM, which in turn delayed embryonic development and the delivery.